Enzyme Engineering Enables Inversion of Substrate Stereopreference of the Halogenase WelO5*. Issue 24 (18th November 2022) - Voss, Moritz; Hüppi, Sean; Schaub, Daniela; Hayashi, Takahiro; Ligibel, Mathieu; Sager, Emine; Schroer, Kirsten; Snajdrova, Radka; Buller, Rebecca
Abstract: Enzymatic late‐stage diversification of small molecules has the potential to rapidly generate diversity in compound libraries dedicated to drug discovery. In this context, freestanding Fe(II)/α‐ketoglutarate‐dependent halogenases have raised particular interest as this enzyme family allows the otherwise difficult regio‐ and stereoselective halogenation of unactivated C(sp 3 )−H bonds. Here, we report the development of two engineered variants of the halogenase WelO5* for the racemic resolution of a mixture of stereoisomers generated in the synthesis of a bioactive martinelline‐derived fragment. By screening a 3‐site combinatorial variant library, we could identify two variants exhibiting exquisite substrate selectivity towards the desired enantiomers. Strikingly, the inversion of substrate stereopreference between the halogenase variants was achieved by varying only three residues in the active site. Protein crystallization and subsequent structure elucidation of the wildtype enzyme and a WelO5* variant shed light on the factors governing substrate acceptance and selectivity. Abstract : Enzymatic kinetic resolution by variants of the halogenase WelO5* allows for the selected chlorination of two martinelline‐derived fragments. Strikingly, these engineered enzyme variants differ by only three strategically selected amino residues in the active site. In addition, the protein structure elucidation of WelO5* provides information about the substrate coordination of this enzyme and underlines the flexible nature of the C‐terminal helix.